STRATEGI PELAYANAN ANAK AUTIS DI PUSAT LAYANAN AUTIS KUPANG NUSA TENGGARA TIMUR - Dian R. Prihanto; Ezra Tari; Hendrik A.E. Lao (Program Studi Bimbingan dan Konseling, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2021)
Autistic children are children with certain limitations who must get guidance and support from parents and people who have expertise in therapy for autistic children so that they are not excluded. This research aims to develop a service strategy for children with autism in the East Nusa Tenggara autism service centre. The research method used is a phenomenological method with a qualitative approach. The subject of this research involved four therapists with data analysis techniques, interviews and documentation, data analysis techniques using data analysis techniques. The results showed that autistic children with symptoms selected by several factors, especially prenatal, natal and postnatal factors, were following the initial diagnosis results of psychologists, doctors or psychiatrists and autistic children who were still in the mild autistic category. The assessment carried out at the NTT Autistic Children Service Center has been carried out according to the steps expected, starting from initial recruitment and parents filling in questionnaires and then being assessed by psychologists and doctors to see the level of children's autism. Supportive therapy regarding existing services in autism service centres is behavioural and aquatic to train the concentration and nerves of children with autism to show significant changes.